1995
DOI: 10.1007/bf02367781
|View full text |Cite
|
Sign up to set email alerts
|

Induction and intracellular localization of a 72-kDa heat shock protein in rat gastric mucosa after water-immersion stress

Abstract: We investigated the expression and changes in the intracellular localization of a 72-kDa heat shock protein (HSP72) in rat gastric pyloric and fundic mucosa before and after water-immersion stress. Severe mucosal damage was found in the fundic mucosal area of the stomach after this stress. However, no mucosal lesion developed in the pyloric mucosal area. HSP72 in both the soluble and insoluble fractions of the pyloric and the fundic mucosal areas was significantly increased after water-immersion stress, peakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…A number of previous observations have suggested that HSPs, especially HSP70, play an important role in protecting gastric mucosa against the development of lesions (17,18,(33)(34)(35)(36)(37)(38)(39). However, prior to the current study, little direct evidence, genetic or otherwise, existed to support this idea.…”
Section: Discussionmentioning
confidence: 62%
“…A number of previous observations have suggested that HSPs, especially HSP70, play an important role in protecting gastric mucosa against the development of lesions (17,18,(33)(34)(35)(36)(37)(38)(39). However, prior to the current study, little direct evidence, genetic or otherwise, existed to support this idea.…”
Section: Discussionmentioning
confidence: 62%
“…It showed that 400 probes, including 5 genes associated with HSP70 and the heat-shock transcription factor-1 gene, were up-regulated at least 1.5-fold after a 6-hour exposure to indomethacin (500 µ M ) in comparison with the vehicle-treated cells. In the gastric mucosa, the cytoprotective ability of HSP70 in vivo and in vitro has been reported [15,16,17,18]. On the other hand, Jin et al [19 ]reported that the pre-induction of HSP did not have a cytoprotective function in small-intestinal damage caused by indomethacin.…”
Section: Discussionmentioning
confidence: 98%
“…Artificial up-regulation of HSPs, especially HSP70, by GGA (a clinically used antiulcer drug) or other methods in cultured gastric mucosal cells confers protection from irritant-induced cell death (Nakamura et al, 1991;Hirakawa et al, 1996;Mizushima et al, 1999;Tomisato et al, 2000Tomisato et al, , 2001Takano et al, 2002), whereas exposure to such irritants induces HSP production (Zeniya et al, 1995;Otani et al, 1997;Itoh and Noguchi, 2000;Saika et al, 2000). In this study, we found that HSF1-null mice are more susceptible to irritant-induced gastric lesions, providing direct genetic evidence for the significance of HSPs in ameliorating the outcome of irritant-induced gastric insults.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported not only that various gastric irritants, including ethanol, up-regulate HSPs, but also that artificial up-regulation of HSPs confers resistance to these irritants in cultured gastric mucosal cells (Nakamura et al, 1991;Hirakawa et al, 1996;Mizushima et al, 1999;Saika et al, 2000;Tomisato et al, 2000Tomisato et al, , 2001. Similar up-regulation of HSPs by gastric irritants has also been recorded in vivo, in addition to which whole-body heat treatment has been shown to suppress gastric irritant-induced lesions (Zeniya et al, 1995;Otani et al, 1997;Itoh and Noguchi, 2000;Saika et al, 2000). Although these findings strongly indicate that HSPs are protective, very little direct evidence exists, and to date, no in vivo study has been conducted to demonstrate that inhibition of HSPs results in a phenotype susceptible to irritant-induced gastric lesions.…”
mentioning
confidence: 82%